Responsibility Of Children As Perpetrators Of Criminal Acts Of Abuse That Cause The Death Of Minors - Choirunnisa, Choirunnisa; Hilman, Didi; Lestari, Nisa (JURNAL MAHASISWA YUSTISI, 2024)
One of the crimes of abuse that was committed by a child until the victim died, occurred in the jurisdiction of the Bogor City District Court with Decision Number 11/Pid.Sus-Anak/PN.Bgr, as the child who committed the abuse resulted in the victim's death. For the actions committed by the child as the perpetrator of a crime, the judge sentenced the child to 9 years in prison. The aim of this research is to determine the factors that cause children to commit criminal acts of abuse which cause death, criminal liability by children who commit abuse which causes death, as well as the application of sanctions to children who commit criminal acts of abuse which cause death in the Decision of the Bogor City District Court Number.11/Pid. Sus-Anak/PN.Bgr. The type of research used is normative juridical research using a statutory approach and a case approach, which is supported by data obtained from the literature, including books, statutory regulations and court decisions, and in this case the data is processed using qualitative analysis. Based on the research results, the factors that cause children to commit criminal acts of abuse that cause death include several factors, both internal and external factors. Criminal liability by children who are perpetrators of abuse that causes death can be seen as stipulated in Article 351 paragraph (3) of the Criminal Code, as criminal liability is imposed on the child when it is proven that the criminal elements have been fulfilled in the form of an error committed by the child, abuse that occurs. was properly carried out by the child, and the victim who was the victim of the abuse was known to have died during or after the abuse which resulted in death in the Decision of the Bogor City District Court Number.11/Pid.Sus-Anak/PN.Bgr, namely imposing a prison sentence to the child, therefore with a prison sentence of 9 years